2018
DOI: 10.3389/fonc.2018.00363
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulotoxicity Associated With Platinum-Based Chemotherapy in Survivors of Cancer: A Scoping Review

Abstract: Background: Cochleotoxicity following the treatment with platinum-based chemotherapy is well documented. The potential for vestibulotoxicity is still unclear. This scoping review examined the extent of current research literature, summarized research findings and identified research gaps regarding vestibular-related adverse effects associated with platinum-based chemotherapy in survivors of cancer.Methods: Inclusion criteria followed the PICO principles: Participants, adult, and pediatric cancer patients of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 58 publications
(173 reference statements)
0
44
1
Order By: Relevance
“…Kneis et al 2020 is the only postural study that assessed vestibular function, finding no vestibular dysfunction in their cohort. However, the rate of abnormal vestibular function after chemotherapy ranges from 0 to 50% [ 45 ]. Furthermore, Wampler et al 2007 found two of the largest postural sway differences between cancer survivors and controls occurred in standing conditions relying on vestibular input, suggestive of vestibular impairments [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kneis et al 2020 is the only postural study that assessed vestibular function, finding no vestibular dysfunction in their cohort. However, the rate of abnormal vestibular function after chemotherapy ranges from 0 to 50% [ 45 ]. Furthermore, Wampler et al 2007 found two of the largest postural sway differences between cancer survivors and controls occurred in standing conditions relying on vestibular input, suggestive of vestibular impairments [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could be because the degree of otolith dysfunction appears to be less than that of canal dysfunction in bilateral vestibulopathy [16]. None of the studies evaluated otolith function by VEMP in cancer populations who received cisplatin chemotherapy [12]; therefore, its utility has not yet been fully investigated.…”
Section: Diagnosis Of the Cisplatin Vestibulotoxicitymentioning
confidence: 99%
“…Balance problems such as dizziness and unsteadiness can cause significant negative impact on quality of life [9] and substantial economic burden [10], especially in a vulnerable group of cancer survivors [11]. Whilst the existence of cisplatin vestibulotoxicity is evident [12], the extent, severity, and impact are largely unclear from the literature, and seem to be under-reported and under-investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular effects associated with platinum-based chemotherapy are less frequently described in the literature compared to auditory symptoms, but can be debilitating [5]. Vestibular dysfunction can trigger a deterioration of quality of life including physical impairment that interfere with driving, riding a bicycle, and other activities involving good balance, as well as psychological symptoms [53].…”
Section: Vestibular Symptomsmentioning
confidence: 99%
“…Despite potent efficacy against cancer, ototoxic effects are significantly problematic which limit usage and dosage [2]. Cisplatin has been found to be the most ototoxic agent in the platinum-based chemotherapy group with associated hearing loss [3], tinnitus [4], and imbalance [5]. Carboplatin and oxaliplatin have been demonstrated to be less ototoxic [6], though audiovestibular issues still arise.…”
Section: Introductionmentioning
confidence: 99%